Enhancing the Anti‐Solvatochromic Two‐Photon Fluorescence for Cirrhosis Imaging by Forming a Hydrogen‐Bond Network - Ren, Tian‐Bing; Xu, Wang; Zhang, Qian‐Ling; Zhang, Xing‐Xing; Wen, Si‐Yu; Yi, Hai‐Bo; Yuan, Lin; Zhang, Xiao‐Bing (Angewandte Chemie, 2018)
Two‐photon imaging is an emerging tool for biomedical research and clinical diagnostics. Electron donor–acceptor (D–A) type molecules are the most widely employed two‐photon scaffolds. However, current D–A type fluorophores suffer from solvatochromic quenching in aqueous biological samples. To address this issue, we devised a novel class of D–A type green fluorescent protein (GFP) chromophore analogues that form a hydrogen‐bond network in water to improve the two‐photon efficiency. Our design results in two‐photon chalcone (TPC) dyes with 0.80 quantum yield and large two‐photon action cross section (210 GM) in water. This strategy to form hydrogen bonds can be generalized to design two‐photon materials with anti‐solvatochromic fluorescence. To demonstrate the improved in vivo imaging, we designed a sulfide probe based on TPC dyes and monitored endogenous H2S generation and scavenging in the cirrhotic rat liver for the first time. Zweiphotonenfarbstoffe mit antisolvatochromer Fluoreszenz, optisch einstellbaren Gruppen, hohen Fluoreszenzquantenausbeuten und großem Zweiphotonenwirkungsquerschnitt werden vorgestellt. Sie können zur In‐vivo‐Bildgebung von endogenen H2S‐Erzeugungs‐ und Abfangprozessen in Rattenleber mit Zirrhose eingesetzt werden.